CORPORATE SOCIAL RESPONSIBILITYA DIRE NEED - Chopra, Ms.Nancy (IJRDO - Journal of Social Science and Humanities Research, 2016)
Corporate social responsibility (CSR) is gaining more and more importance day by day. CSR is not only drawing the corporate magnates into its circumference, but is also luring educationists, social activists,reformists, from all over the world to delve deeper into it. Changing market scenario, globalization,ethical consumerism all are adding heat to the CSR concept. More and more organizations are showingtheir commitments towards CSR either for enhancing their corporate image or to be in competition.Emergence of different marketing innovations demands direct linkage of corporate social responsibilitypractices with the business corporate strategies.